Growing Population of Pakistani Youth: A Ticking Time Bomb or a Demographic Dividend (Journal of Education and Educational Development, 2020)
Pakistan is considered to be the fifth largest young country in the world. Around 63 percent population of the country comprises youth aged between 15 and 33 (UN Population Fund Report 2017). Such a large young population has posed daunting challenges to the social, economic and political sectors of the state. The fast rising youth bulge of Pakistan seems to be a constantly ticking time bomb instead of a demographic dividend, threatening its very own existence. Poor youth engagement in the productive political, educational, economic and socio-cultural activities indicates ineffectiveness of the public and private sectors policies especially at the state level. The current research study is intended to identify the key factors behind the disengaged and distressed youth of Pakistan in the three core areas of education, economy and politics. For this purpose, a systematic literature review was carried out in which national and international labor survey reports, youth development index, national youth program and federal education and economic policies were critically analyzed alongside the relevant research studies, nongovernment organizations’ reports and media coverage for a dynamic overview. Besides, interviews of relevant stakeholders were also conducted to investigate the issue from diverse perspectives. Evidently, youth partnership, empowerment, and engagement in educational, economic and political sectors can be the only way forward to address the increasing challenges of the country.